1996
DOI: 10.1111/j.1365-2702.1996.tb00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric nursing and research ethics: is there a conflict?

Abstract: This paper briefly outlines the major ethical issues which need to be considered when conducting paediatric research. An overview of ethical theories and principles will highlight the difficulties which may be experienced when making decisions about children's competency to consent to participate in research. The congruency of the paediatric nurse as 'researcher' and 'practitioner' will be examined. Does the nurse involved in paediatric research experience a conflict between a commitment to research and safegu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Children may agree to take part merely to please, and/or because they have learnt to respect and obey adults. 36,[85][86][87] Ondrusek et al found that, regardless of age, children's belief that the researcher would be unhappy if they withdrew from the research possibly prevented children from withdrawing from the study. 72 This highlights the importance for researchers to ensure that children are aware that the researcher will not be upset if they withdraw.…”
Section: Children's Voluntary Participation (In Theory)mentioning
confidence: 99%
“…Children may agree to take part merely to please, and/or because they have learnt to respect and obey adults. 36,[85][86][87] Ondrusek et al found that, regardless of age, children's belief that the researcher would be unhappy if they withdrew from the research possibly prevented children from withdrawing from the study. 72 This highlights the importance for researchers to ensure that children are aware that the researcher will not be upset if they withdraw.…”
Section: Children's Voluntary Participation (In Theory)mentioning
confidence: 99%